Burnout in secondary school teachers (Research, Society and Development, 2020)
The aim of this study was to investigate the incidence of burnout in Mozambican teachers in general secondary education, verifying possible associations with sociodemographic and labor variables. The sociodemographic data questionnaire and the Maslach Burnout Inventory - Educador Survey, Portuguese version, were applied to 250 teachers from two public secondary schools. Statistical data analysis showed that teachers have a moderate average of Emotional Exhaustion - EE (2,68) and Depersonalization - DE (2,51) and high Professional Achievement - PA (3.26). Age, number of children and professional experience were variables that showed positive correlations with the dimensions EE and DE and the number of children was negatively associated with PA. Single teachers had a high average in PA (M = 3,56; SD = 1,27) in relation to the others. Thus, it is worth emphasizing the need to design prevention and intervention programs, since teachers are in the stage of developing burnout.